Knowledge, attitudes, and practices of COPD patients regarding acute exacerbations of COPD - Xia, Yuan; Zhang, Yahua; Su, Dan (Frontiers in Medicine, 2025)
ObjectiveThis study aims to assess the knowledge, attitudes, and practices (KAP) of patients with chronic obstructive pulmonary disease (COPD) concerning AECOPD.MethodsA cross-sectional survey was conducted at Yuexi County Hospital in Anhui Province, China, between April and December 2024. Data were collected using a structured questionnaire comprising demographic characteristics and KAP assessments. Adequate knowledge, positive attitudes, and proactive practices were defined as achieving at least 60% of the maximum possible score in each domain.ResultsA total of 445 valid questionnaires were analyzed. Among the respondents, 332 (74.61%) were male, and 271 (60.90%) had been diagnosed with COPD for over a decade. The mean scores for knowledge, attitude, and practice were 7.25 ± 4.43 (range: 0–26), 36.91 ± 4.56 (range: 11–55), and 30.59 ± 3.76 (range: 10–50), respectively. Correlation analysis showed positive correlation between knowledge and attitude (r = 0.095, p = 0.045), knowledge and practice (r = 0.376, p < 0.001), and attitude and practice (r = 0.324, p < 0.001). SEM analysis demonstrated that knowledge directly influenced both attitude (β = 0.226, p = 0.036) and practice (β = 0.660, p = 0.008), while attitude also had a direct effect on practice (β = 0.299, p = 0.004). Additionally, knowledge exerted an indirect effect on practice through attitude (β = 0.067, p = 0.020).ConclusionDespite generally positive attitudes and proactive practices, COPD patients exhibited insufficient knowledge about AECOPD, which may limit their ability to effectively manage exacerbations. Targeted education may enhance self-care and reduce exacerbation risk.